Inclusión de la etnoeducación en la conservación de los saberes ancestrales. - Cabezas, Katya M. (2022)
The article reveals the complexity of ethnic education from a quantitative approach; being the purpose, inclusion of ethnic education in the conservation of ancestral knowledge. The reality determines that ethno-education consists mainly of the right of Ecuadorian ethnic peoples, despite the argument that has been used, ethnoeducational material has been disseminated in order to weaken its invisibility, and support has been sought for its dissemination from different ethnic groups, especially the Afro-Ecuadorian people. The research seeks arguments about the need for ethnoeducation to become a relevant educational instrument to generate a reinforcement of what concerns national ancestral knowledge, in addition to combating structural racism and various scenarios of discrimination that are latent. in our territory. In this article, an analysis of the actions related to the process of incorporation of ethnic education of Afro-Ecuadorians in terms of the curriculum was carried out. In order to know the opinion about its incorporation in the curriculum, teachers from the San Lorenzo canton were consulted, with the purpose of knowing their criteria regarding the importance of ethnic education. The work includes a theoretical support and the study of art on ethnic education. The research approach is quantitative, and to obtain this type of data, a structured survey using the Likert scale was applied to 151 teachers. The results achieved determine the need to include the subject of ethnic education and thus preserve ancestral knowledge.